2011
DOI: 10.1038/ijo.2011.39
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of the 3DNX accelerometer during mechanical and human treadmill exercise testing

Abstract: Objective: This study aimed to assess the validity and reliability of the 3DNX triaxial accelerometer in a laboratory and mechanical setting. Methods: Experiment 1: A total of 10 units were fixed to a Multi-axis shaker table. A schedule comprising a range of accelerations was repeated on two occasions along each of the three measurement axes. Experiment 2: A total of 11 recreationally active individuals completed a treadmill protocol (4-20 km hr À1 ) on two occasions. Two 3DNX accelerometers were secured to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
2
7
0
Order By: Relevance
“…In our study, the ICC observed across testing conditions were high and concurred with those reported for other available accelerometers (18,26) and previous generations of ActiGraph (5). If interunit reliability is poor, then it becomes difficult to distinguish whether the variability in PA during free-living monitoring between subjects is solely attributed to variations in behavior or inherent to the accelerometer.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In our study, the ICC observed across testing conditions were high and concurred with those reported for other available accelerometers (18,26) and previous generations of ActiGraph (5). If interunit reliability is poor, then it becomes difficult to distinguish whether the variability in PA during free-living monitoring between subjects is solely attributed to variations in behavior or inherent to the accelerometer.…”
Section: Discussionsupporting
confidence: 88%
“…The weak relation of R s = 0.25 between 0.06g and 1.5g is well below that of most industry-standard PA monitoring accelerometers. The GENEA and 3DNX PAC outputs are both strongly related to acceleration during a mechanical setup, with correlations of r = 0.97 and r = 0.99, respectively (10,18). In the older 7164 model ActiGraph, Brage et al (5) unequivocally stated that count output is only proportional to acceleration if frequency is held constant, implying that some form of frequency-dependent filter exists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accelerometer reliability is subject to technical (eg, inconsistencies in capturing signals and processing data) and human-related (eg, accidental altering of the position of device) sources of random error. Accelerometers demonstrated high intrainstrument and interinstrument reliability in mechanical laboratory settings, with coefficients of variation (CV) mostly below 5% and 10%, respectively,34–43 and when assessing structured activities in controlled laboratory conditions, with most intraclass correlation coefficients (ICCs) ranging from 0.60 to 0.90 36 42 44–48. Interinstrument reliability of accelerometers in free-living conditions ranged from mediocre for RT3 accelerometers (CV 9.8–39.8%)49 to relatively high for Actigraph 7164 and GT1M models (CV 0.9–15.5%) 49 50.…”
Section: Suitability Of Accelerometry For Pa Surveillancementioning
confidence: 99%
“…This supplement contains many studies carried out to ensure the quality and rigour of measures included in the IDEFICS study. This measurement rigour has been applied to diet 8,9 and physical activity, [10][11][12] as well as to measurement of social and biological determinants [13][14][15] and health consequences. [16][17][18][19][20] Furthermore, the detailed description of both the strengths and limitations with regard to measurement selection and development is an important resource for dissemination, given its potential for shaping future studies.…”
mentioning
confidence: 99%